Improving tea quality and fruit yield through intercropping with climbing plants - Liao, Qing; Xing, Ying; Chen, Jin-Ping; Mou, Hai-Fei; Tian, Qing-Lan; Wang, Lei; Guo, Li-Xia; Liang, Pan-Xia; Liu, Zhu-Sheng (Frontiers in Agronomy, 2025)
Integrating high-value climbing fruit crops into tea (Camellia sinensis) systems offers potential to improve tea quality and diversify income, yet the density-dependent effects on both crops remain unquantified. This study evaluated tea intercropped with Siraitia grosvenorii (SG) and Passiflora edulis (PE) at three planting densities (low, medium, high), assessing tea leaf biochemical traits alongside fruit physical and intrinsic quality parameters. All intercropping treatments significantly increased tea leaf chlorophyll a, b, and total chlorophyll content compared with monoculture (CK), with maxima in PE-H (1.188, 0.447, and 1.635 mg/g) and SG-H (1.166, 0.425, and 1.591 mg/g), respectively. Tea polyphenol content decreased with increasing density, most notably in PE-H (−21.63% vs. CK), while free amino acids increased under SG-M (+20.50%) and PE-L (+19.10%). The polyphenol-to-amino acid ratio declined across treatments, with the largest reductions in PE-L (−24.36%) and SG-M (−19.62%). Water extract content rose in all intercropped systems, peaking in SG-H (+5.82%) and PE-H (+2.12%). For S. grosvenorii, SG-H achieved the highest single-fruit weight (94.37g), transverse diameter (54.56mm), proportion of medium/large fruits (94.58%), and sugar contents (reducing sugar 6.69%, total sugar 12.01%). For P. edulis, PE-H produced the highest soluble solids (17.82%), soluble sugars (12.27%), solid-acid ratio (6.72), and sugar-acid ratio (4.62), indicating superior flavor, whereas PE-M maximized titratable acids (2.74%) and peel thickness (5.16mm), and PE-L yielded the highest edible ratio (46.68%). This work provides density-resolved evidence that tea-climbing plant intercropping can simultaneously enhance tea leaf quality, and improve fruit sweetness and flavor profiles. Optimal densities vary by species, offering a dual-quality, agroecologically viable model for tea-based polyculture.